Electrospinning : A Practical Guide to Nanofibers - Agarwal, Seema; Burgard, Matthias; Greiner, Andreas; Wendorff, Joachim (De Gruyter Textbook, 2016)
Focuses on basic aspects of nano/microfibers made by electrospinning with details on spinning recipes, characterization techniques and chemistry of the polymers in use. The basic understanding provided in the book, is useful for producing 1D and 3D fibrous structures with specific properties for applications, e.g. textiles, membranes, reinforcements, catalysis, filters or biomedical uses. Students and practitioners will find great value in the step by step instructions how to manufacture nanofibers. - Electrospinning equipment- History of electrospinning and nanofibers -characterization-fundamentals of electrospun fibers- Ready-made recipes for spinning solutions- Conditions for the productions of highly diverse fiber morphologies and arrangements- Chemistry of fiber forming materials